(untitled) (Journal of the College of Basic Education, 2022)
The theory of multiple intelligences has revolutionized the educational and educational fields. Gardner has directed the view to the energies of each individual, which, if trained well, will generate a generation of talented and distinguished people who have multiple and varied methods for solving problems and have the ability to adapt to different situations and have multiple ways to deal with data The era and its variables (Al-Ansari and Al-Feel, 2009: 175).With the birth of the Multiple Intelligences theory, our understanding of the nature of human intelligence has increased in depth, so that a person has a set of intelligences, not a single one. None of us can deny the importance of multiple intelligence in different areas of life, whether in the field of education, in the field of training, or in various social or life situations. The issue of placing the right man in the right place requires knowledge of the individual’s mental capabilities and also requires knowledge of work requirements to ensure The success of the individual in his work, and in light of the foregoing, the research problem can be summarized in the following question:Linguistic intelligence is one of the types of multiple intelligence that has received great attention from psychologists and education, and this interest has played a major role in relying on the use of linguistic intelligence strategies and activities in the learning process. Gardner (1983) referred to linguistic intelligence, using poetry and creative writing as examples of this type of intelligence or talent. Scientists, historians, critics, novelists and all researchers, but some of them use language better than others, and this confirms that these people all have a degree of talent.Linguistic intelligence obtained the largest share among researchers’ interests in multiple intelligences. Gardner ranked linguistic intelligence in the first place, and considered it one of the most important intelligences that help the learner to develop other intelligences, from which the researcher’s question comes, as follows:Does joining kindergarten have a role in developing the linguistic intelligence of first graders?